Pneumothorax in Neonates Born to COVID-19–Positive Mothers: Fact or Fortuity? - Kamity, Ranjith; Nayak, Amrita; Dumpa, Vikramaditya (American Journal of Perinatology Reports, 2021)
Neonates born to mothers with coronavirus disease 2019 (COVID-19) have been largely asymptomatic based on initial reports. All neonates born to mothers with COVID-19 have tested negative for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in our institution (published data as of April 12, 2020). As novel presentations of COVID-19, such as multisystem inflammatory syndrome in children are being increasingly reported, we raise the possibility of increased incidence of pneumothorax in neonates born to SARS-CoV-2–positive mothers. Two recently described neonates with COVID-19 infection were noted to have pneumothoraces. We describe two SARS-CoV-2–negative neonates born to COVID-19–positive mothers at 38 and 33 weeks, respectively, admitted to our neonatal intensive care unit for respiratory distress and subsequently developed pneumothoraces. As diverse clinical presentations in various age groups are being described, it becomes difficult to differentiate the increased incidence of complications related to an underlying illness, from COVID-19–related illness. It remains to be seen if neonates with in utero exposure to SARS-CoV-2 have an elevated inflammatory response with pneumonitis and exaggerated lung disease, similar to adult COVID-19 patients, due to in utero exposure.
Keywords: COVID-19; coronavirus disease 2019; neonate; pneumothorax; SARS-CoV-2; vertical transmission